Online Communication And PR in Romanian Public Administration. The Case Study of Public Institutions From Transylvania - Delia Cristina BALABAN; Mirela Codruţa ABRUDAN; Ioana IANCU; Cosmin IRIMIEŞ (Transylvanian Review of Administrative Sciences, 2016)
New technologies such as Internet and new media introduce new challenges for public communication. Private companies from Romania use in a very creative way the new tools of Web 2.0, such as social media. In the Romanian public sector, especially in the public administration there are important steps taken towards a modern communication. Based on the example of over 40 city halls, city councils, prefectures and county councils from Transylvania, the present paper analyzes the use of new media tools in public communication by applying content analysis and in-depth interviews with the PR representatives in those institutions in two stages, 2011 and 2015. The most important advantages of online communication in public administration are high speed, cost reduction, reaching young audiences, etc. Nevertheless, there are also critical voices that express possible risks such as exclusion of audience groups that have no online media literacy.